Desentrañando el “misterio” de África: el “afropesimismo” como discurso hegemónico en el contexto de la pandemia del COVID-19 - Dias Pereira, Luiz Felipe (El Colegio de México A.C., 2022)
This research focuses on the performance of African countries with regard to public health policies in the context of the covid-19 pandemic (2020-2021). The main argument is that the response of African countries to the pandemic and the low number of deaths on the African continent in general made explicit a contradiction in the hegemonic discourse regarding African states’ capacity to act effectively in the face of the threat of the virus. The theoretical framework includes post-structuralist and post-colonial approaches of International Relations and the methodology consists of discourse analysis.